A-46 Deconstructing Competitiveness: The Effect of Age on Athlete's Desire to Succeed, Win, and Achieve Goals. (18th June 2020) - Webber, A M; Wong, R E; Du Plessis, S; Garcia-Barrera, M A
Abstract: Objective: Our previous research indicated that athletes scoring high in competitiveness were less likely to report sports-related concussion symptoms and withdraw from the game. The present study examined whether athletes' desire to succeed (competitiveness motive), win (win orientation), and achieve personal goals (goal orientation) were related to the age of players. Method: Participants included 161 athletes, ages 14–32 (M = 17.6 years; 33.2% female), recruited from a mid-sized Canadian city participating in low (rowing), moderate (soccer) and high (hockey, rugby, football) contact sports. Confirmatory factor analysis was first used to evaluate the structure of the Sports Orientation Questionnaire. Then, using SEM, athletes' competitiveness, goal orientation, and win orientation were predicted by age. Results: High internal consistency was obtained within each factor (.84–.93). The model demonstrated suboptimal fit for this sample (CFI = .84; χ2f/ df ratio = 2.02; RMSEA = .087; 90% CI: .077–.097). All factors were significantly related to age, indicating that athletes' desire to succeed (competitiveness motive; β = .18, p = .009), achieve personal goals (goal orientation; β = .26, p = .007), and win (win orientation; β = .30, p = .000) increases with age. Conclusion: The small positive association between age and competitiveness, win, and goal orientation indicates that older athletes are more competitive than younger athletes. Given that competitiveness predicts athletes' intention to report a concussion, clinicians and coaches should pay particular attention to senior athletes who demonstrate high levels of general competitiveness and who are driven by the desire to win and achieve personal goals. Therefore, interventions targeting the barriers to reporting concussions should evaluate subco.